2011
DOI: 10.1007/s00415-011-5946-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dysautonomia in extrapyramidal disorders

Abstract: Although extrapyramidal diseases are commonly thought to solely affect the (extrapyramidal) motor system, non-motor symptoms such as behavioural abnormalities, dysautonomia, sleep disturbances and sensory dysfunctions are also frequently observed. Autonomic dysfunction is an important clinical component of extrapyramidal disease, but it is often not formally assessed, and thus frequently misdiagnosed. Symptoms of autonomic dysfunction can impact more on quality of life than motor symptoms. Appropriate symptom-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 72 publications
0
22
0
11
Order By: Relevance
“…It was also suggested that UCN served to maintain sufficient functions of nigra-striatum neurons by influencing CRF receptors (Bale and Vale, 2004;Colosimo et al, 2010). These findings were of great potential significance in the treatment of PD induced by the degeneration of nigra-striatum neurons (Ziemssen et al, 2011). Our experiments suggested that in the pathological condition of PD or epilepsy, UCN2 might inhibit high frequency discharge of STR neurons and suppress GLU neuronal toxicity, thereby constraining the occurrence and development of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…It was also suggested that UCN served to maintain sufficient functions of nigra-striatum neurons by influencing CRF receptors (Bale and Vale, 2004;Colosimo et al, 2010). These findings were of great potential significance in the treatment of PD induced by the degeneration of nigra-striatum neurons (Ziemssen et al, 2011). Our experiments suggested that in the pathological condition of PD or epilepsy, UCN2 might inhibit high frequency discharge of STR neurons and suppress GLU neuronal toxicity, thereby constraining the occurrence and development of the disease.…”
Section: Discussionmentioning
confidence: 87%
“…This screening should include a standardized autonomic questionnaire [33], an active standing test and 24 h ABPM [26]. In the case of pathological findings, detailed autonomic testing should follow including spectral and baroflex analysis as well as passive orthostasis for the quantification of orthostatic hypotension and of supine hypertension [34]. In addition, pupillography demonstrating miosis is most useful for the diagnosis of PSP [9].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of dysautonomia in PD patients is quite variable depending on the study population and methodology, ranging from 14% to 80%. 13 In a casecontrol study on 141 patients with PD and 50 age-matched controls, it was observed that the incidence of orthostatism (48% vs. 22%), bladder dysfunction (45% vs. 24%), erectile dysfunction (64% vs. 20%), and hyperhidrosis (46% vs. 22%) was significantly higher in the former, and in at least 50% these symptoms greatly altered the quality of life. 14…”
Section: Autonomic Symptomsmentioning
confidence: 97%